Introduction to Microsystem Design - Schomburg, Werner Karl. (RWTHedition,, 2015)
This book systematically describes the design options for micro systems as well as the equations needed for calculating the behavior of their basic elements. The fundamental equations needed to calculate the effects and forces that are important in micro systems are also provided. Readers do not require previous knowledge of fabrication processes. This second edition of the volume is a thoroughly revised and extended update. The target audience primarily comprises experts in the field of micro systems and the book is also suitable for graduate engineering students. For quick reference, equations are presented in tables that can be found in an index at the end of the book.  .